If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2)(5x + 4) * x = 0 Reorder the terms: (2 + 3x)(5x + 4) * x = 0 Reorder the terms: (2 + 3x)(4 + 5x) * x = 0 Reorder the terms for easier multiplication: x(2 + 3x)(4 + 5x) = 0 Multiply (2 + 3x) * (4 + 5x) x(2(4 + 5x) + 3x * (4 + 5x)) = 0 x((4 * 2 + 5x * 2) + 3x * (4 + 5x)) = 0 x((8 + 10x) + 3x * (4 + 5x)) = 0 x(8 + 10x + (4 * 3x + 5x * 3x)) = 0 x(8 + 10x + (12x + 15x2)) = 0 Combine like terms: 10x + 12x = 22x x(8 + 22x + 15x2) = 0 (8 * x + 22x * x + 15x2 * x) = 0 (8x + 22x2 + 15x3) = 0 Solving 8x + 22x2 + 15x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(8 + 22x + 15x2) = 0 Factor a trinomial. x((4 + 5x)(2 + 3x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(4 + 5x)' equal to zero and attempt to solve: Simplifying 4 + 5x = 0 Solving 4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 0 + -4 5x = 0 + -4 Combine like terms: 0 + -4 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8Subproblem 3
Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667Solution
x = {0, -0.8, -0.6666666667}
| 9x^2=-2x+2 | | 30+4L=100 | | 3t-10=28 | | 5(3.2+0.2y)+y=16 | | -4(-3+10x)-7(x-10)=-11x+5x | | 10y-7y-5=52.72 | | (a)-13+24= | | 3.2+0.2y+y=16 | | x+(x+6)=120 | | b/r–c/r=1 | | 8=5-3g | | 29/18/4/9 | | 4x^2=12x^2-24x | | -2/5v-3/5=6v-1/2 | | (9x+2)*(2x+1)=0 | | -1/4-(-9/20) | | -4+3.2x-6= | | 7(-22/3)-2((-22/3)-7) | | 6-18-18x=0 | | 6-36x=0 | | 56+x=44 | | 23x-13y=-11 | | 3-3w=9 | | 3(6x+9-9)+8=70-2x | | (3g-2h)(8)=0 | | 2/3=9/x | | 1/3(6x-9)=4x-5 | | 14=2(8)+1 | | x+-24=18 | | 1/3(6x-9)=4c-5 | | 16/(2x^2) | | 4p^2-6p-5=0 |